CHARACTERISTICS AND INTERTEXTUALITY OF MAYA ANGELOU’S POEMS - I PUTU RAMADHANY Y. (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2015)
Keywords : Characteristics, intertextuality, poems, Maya Angelou Poems as an object of art has its value to delivers its message indirectly and beautiful, like a glimmering or absurd picture in a white canvas. No one really know what its true meanings or being riddled by many puzzles of words. This magnificent of art has its own form, foundation, form, shape and method, texture and structure to drew a lot of its potential artistic, which obviously would be a matter of choice that would be chosen by who will be its author. And speaking about characteristic in a poem, this is a feature which in a clear bright of crystal will bring a definitive differentiation inside the real person who made it. A character with an honest and sweet scent inside a man might made a poem which in its feature would be in a smooth or a gentle aura. And the opposite person of this man’s character would result a distinctive and different poem as well. In Maya Angelou’s life, If there is a one word to represent her unique characteristic inside her, that would be a thing as struggle fighting against injustice. Born as an African American woman, the little Maya Angelou yet tough must had her life being full of tragedy despair, discrimination, injustice and of course “struggle” itself. Her journeys as she lived an ever changing events in many of her life, were reflected and flowed in many parts of her poems. Reminding us about what had been happened in the eyes of a person called Maya Angelou. Based on these conditions, the analysis of this thesis is grounded on these two main questions:(1) What are the characteristics of Maya Angelou poems? and How is intertextuality in Maya Angelou’s poems?. In supporting the analysis of this thesis some related theories are applied, such as: a basic introduction inside African American feminism, and semiotic theory which based on Michael Riffaterre The effectiveness of using such theories was measured by analyzing the meaning and characteristics which found in Maya Angelou’s poems which based through on her life and settings in her experiences. Also in this thesis the author included the intertextuality between poems created by Maya Angelou herself and another poems which created by the same and different idealistic poets. This result in to what is the distinctive topics or theme between Maya Angelou’s depictions and ideas which formed in her creations and another poets.